Subjective completion beliefs and the demand for post-secondary education - Johannes Kunz; Kevin E. Staub (University of Zurich, Department of Economics, 2016)
The outcome of pursuing a post-secondary educational degree is uncertain. A student might not complete a chosen degree for a number of reasons, such as academic insufficiency or financial constraints. Thus, when considering whether to invest in post-secondary education, students must factor in their completion probability into their decision. We study the role of this uncertainty in educational choices using students' subjective beliefs about completing a post-secondary education, which were elicited prior to students' completing secondary education. We relate these subjective completion probabilities to their subsequent educational choices and outcomes using representative survey data from Germany. Following the students over time, we find that the initial beliefs are predictive of intentions to invest in education, actual subsequent educational investments, and degree completion. We assess the heterogeneity of the impact across different educational paths. After controlling for academic ability, we find that subjective beliefs are most relevant in choosing a vocational education. In addition to reduced form models, we estimate a structural choice model of sequential investment in education that allows for unobserved tastes and preferences for education and forward-looking behavior. The results confirm the influence of subjective completion beliefs on choosing a post-secondary education.
Keywords: I21; I26; J24; 330; Subjective beliefs; educational completion uncertainty; Human Capital Investment